Imagistic thinking of the First Hominids - Galvydis, Juozas (Problemos, 1975)
J. Galvydis expresses his doubt as to the view that the conceptual thinking is immanent to the whole of the human history; he attaches himself to the conception of the imagistic way of thinking of primitive man.